Algorithm of construction of the type and its realization in the language W (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1996)
The notion of polymorphism describes data, which possess more than one type, or functions, which operate over a set of types in programming languages. In this paper an implementation of Milner's polymorphic type interface algorithm is described. It is proved that the algorithm is sound, effective and supports a rich and flexible type system. A programming language with equations and unification W is used.